Social aspects of water management during the Maha season 1985/86 in Dewahuwa and Mahaweli H-2 Block 305: precept and practice - Bulankulame, S. (International Water Management Institute, 1986)
The International Irrigation Management Institute (IIMI) began research projects in Dewahuwa Tank and Mahaweli 11-2 during the Yala season (May-Aug.) of 1985. The research focussed initially on agricultural economics (e.g., farmers' use of agricultural inputs and returns from different crops) and on irrigation engineering (water distribution and flow rates). In the second season (Maha 1985/86) of research a social science component was added to address issues of farmers' management decisions and the institutional arrangements by which farmers and agency officials operate and maintain the irrigation works. This report summarizes the research results of the social science component for the Maha season, from October 1985 to April 1986.